ANALISIS ANALISIS PROFESIONALITAS PENGELOLAAN ZAKAT BADAN AMIL ZAKAT NASIONAL (BAZNAS) TERHADAP PEMBERDAYAAN MUSTAHIQ DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH DI KABUPATEN PANGKEP - Salman Alparizi; Syarifah Raehana; Subaedah Subaedah; Hasanna Lawang; Auliah Alwi; Bahrur Rahman Hasba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Professionalism in zakat management plays a crucial role in improving the effectiveness of mustahiq empowerment through zakat institutions. This study aims to analyze the professionalism of zakat management by the National Amil Zakat Agency (BAZNAS) of Pangkep Regency in empowering mustahiq from the perspective of Islamic Economic Law. This research employed a qualitative approach using a juridical-empirical method. Data were collected through observations, in-depth interviews, and documentation involving BAZNAS administrators and mustahiq beneficiaries. Data analysis consisted of data reduction, data presentation, and conclusion drawing based on the principles of Islamic Economic Law and Law Number 23 of 2011 concerning Zakat Management. The findings indicate that BAZNAS Pangkep Regency has implemented professionalism through transparency, accountability, responsibility, and compliance with Islamic principles in zakat management. The empowerment programs have positively contributed to improving the welfare and economic independence of mustahiq, although several challenges remain, including limited human resources, inadequate zakat collection, and insufficient business assistance. This study concludes that professionalism in zakat management plays an essential role in enhancing the success of mustahiq empowerment programs in accordance with Islamic Economic Law. Therefore, strengthening institutional capacity, improving the competence of zakat administrators, and optimizing productive zakat programs are necessary to achieve sustainable community welfare.